La no tipicación del delito de la clonación de vehículo en el Ecuador. - Ramírez Romero, Sergio Patricio (2013)
Concern as a citizen and student of law, regarding the indiscriminate increase of vehicle theft, and documents of the same, has prompted me to develop the present legal work of investigation, through which I intend to create within the criminal legislation a new crime Autonomous, through which to penalize what we might call cloning.